Tackling text (and subtext) : a step-by-step guide for actors - Houseman, Barbara (Nick Hern, 2008)
This is an intensely practical handbook for students, actors, and teachers on how to cope with text, character, and situation. Barbara Houseman's method is to state a precept and devise an exercise to explore it. The result is a book with a practical exercise on almost every page.